Patterns of adoption of improved maize technologies in Ghana - Ragasa, Catherine; Dankyi, Awere; Acheampong, Patricia; Wiredu, Alexander Nimo; Chapoto, Antony; Asamoah, Marian; Tripp, Robert (International Food Policy Research Institute, 2013)
The study aims to provide up-to-date and rarely collected nationwide data and analysis on the patterns of adoption of improved technologies for maize in Ghana.